PHARMACOPHORE DISTANCE MAPPING AND DOCKING STUDY OF SOME BENZIMIDAZOLE ANALOGS AS A2A RECEPTOR ANTAGONISTS (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Extracellular adenosine regulates a wide range of functions in higher organisms, in which the effects are mediated by a family of four class A (rhodopsin-like) GPCRs, a, adenosine receptors known as A1, A2A, A2B, and A3. A2A antagonists, either alone or in combination with dopamine agonists, can have a role in the treatment of neurodegenerative movement disorders such as Parkinson’s disease and Huntington’s disease. The concept of a pharmacophore is widely used in modern drug design and it is generally defined as the 3D arrangement of certain features in the ligand that are responsible for its activity against a particular protein target. Docking involves, the process of fitting the ligand into receptor, and the compounds which fit in them properly are assumed to be active for that receptor and it gives corresponding docking scores.